POMPA SENTRIFUGAL SEBAGAI TURBIN DENGAN PERFORMANSI HASIL PENGUJIAN LABORATORIUM UNTUK PEMBANGKIT MIKRO HIDRO - Priyono Sutikno (Mesin, 2003)
Pump as Turbine (PaT) tested from mixed flow pump type with 250 mm bore diameter, and impeller tip has a minimum modification by rounded the blade, which could improve the efficiency of 2% to 6%. The modification is done by rounded the impeller tip with 2 mm radius. Tested Pump as Turbine at 1000 rpm has an efficiency about 82% and 10 kW power output. The best power produced by 250 mm bore Pump as Turbine is 25 kW at the 75% efficiency. The 15 meters head may have the runaway speed of the Pump as Turbine on asymptotic level at 2500 rpm. The pump as turbine could utilized as Micro Hydro Power driver in the low cost, compare with Francis turbine design and development cost, which is mass production of the pumps and abundant at the market.